After democracy : imagining our political future - Papacharissi, Zizi (Yale University Press, 2021)
Democracy has long been considered an ideal state of governance. What if it's not? Perhaps it is not the end goal but, rather, a transition stage to something better. Drawing on original interviews conducted with citizens of more than thirty countries, Zizi Papacharissi explores what democracy is, what it means to be a citizen, and what can be done to enhance governance.0 As she probes the ways governments can better serve their citizens and evolve in positive ways, Papacharissi gives a voice to everyday people, whose ideas and experiences of capitalism, media, and education can help shape future governing practices. This book expands on the well-known difficulties of realizing the intimacy of democracy in a global world-the "democratic paradox"--And presents a concrete vision of how communications technologies can be harnessed to implement representative equality, information equality, and civic literacy